PENGEMBANGAN SILABUS DAN RPP MELALUI PEMBINAAN PROFESIONAL DENGAN PENDEKATAN KOOPERATIF BAGI GURU SMPN 21 AMBON - Ida Kurnia L (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2015)
The background of this research is the incapacity of teachers in developing syllabi and lesson plan (RPP). This research is a classroom action research (CAR) at SMP 21 Ambon which aims to improve the competence of teachers in developing the syllabus through professional development with cooperative approach. The study was conducted in two cycles involving collaborators. These results indicated that the ability of teachers/participants in understand-ing of the syllabus and lesson plan (RPP) increased, from an average of 65.31% to 78.75%. The activity teacher/participants also increased which is marked by the increasing boldness of teachers in asking questions and raising such issues and increased cooperation of teachers in developing learning tools, especially for teachers in one subject cluster.Keywords : learning syllabus, lesson plans, Classroom Action Research (CAR).